Histological Features and Predictors of Early Relapse in Patients of Ulcerative Colitis - Momina Jehangir Khan, Fariha Sehrish, Aman ur Rehman, Sahar Iqbal, Anam Ilyas, Rabia Mukhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the proportion of histological features and histological feature predicting frequency of elapse in known patients of ulcerative colitis. Methodology: One hundred and ninety cases each had endoscopic colonic biopsies from the rectum, distal colon, and proximal colon. Study Design: Retrospective Case series Setting: Sheikh Zayed Hospital Lahore, Department of Histopathology, from February 25, 2016, to February 25, 2017. Results: The majority of patients complained of generalized abdominal pain (55.3%). The commonest histological feature is cryptitis 189(99.5%). Majority patients with basal plasmacytosis 38(42.2%) and crypt abscess 36(29.8%) relapsed at 4th month. Conclusion: Histological features basal plasmacytosis and crypt abscess are of prognostic importance. A greater chance of relapse can be predicted in patients with increased number of basal plasma cells and cryptitis. These findings will help in further management of ulcerative colitis patients. Keywords: Inflammatory bowel disease, Ulcerative colitis, Remission, Relapse